Pathophysiology and clinical implications of dengue-associated neurological disorders - Naderian, Ramtin; Paraandavaji, Elham; Maddah, Amir Hossein; Keshavarzi, Saeedeh; Habibian, Anoosha; Naderian, Rayan; Hosseini, Seyed Mohammad; Oksenych, Valentyn; Eslami, Majid (Frontiers in Microbiology, 2025)
Dengue virus (DENV), a mosquito-borne Flavivirus, represents a growing global health challenge, particularly in tropical and subtropical regions. The 2009 WHO classification system for dengue categorizes infections into dengue without warning signs, dengue with warning signs, and severe dengue. This framework highlights the diverse clinical presentations and supports more efficient triage and management of cases. The neurological effects of DENV infection, which include direct neuroinvasion, systemic problems, and immune-mediated sequelae, are a less well-studied but nevertheless important consequence. Guillain-Barré syndrome, acute disseminated encephalomyelitis, myelitis, meningitis, and encephalitis are important neurological symptoms. The dengue classification system improves clinical management by dividing cases into dengue without warning signs, dengue with warning signs, and severe dengue. Mild cases show fever with symptoms like headache and rash, while warning signs include abdominal pain, persistent vomiting, bleeding, and lab changes indicating higher risk. Severe dengue is characterized by critical complications such as shock, severe bleeding, or organ failure. Improved diagnostics aid early detection, and new treatments targeting viral replication and inflammation are being explored alongside supportive care. Although there are still challenges in reaching the ideal vaccination coverage, the introduction of potent vaccines like Dengvaxia and Qdenga provide an achievable option for prevention. Thorough study into DENV’s neurological effects and treatment options is essential as the virus’s geographic range is increased by climate change and international travel. Reducing the worldwide burden of dengue-related neurological complications requires addressing the intricate interactions between virological, immunological, and environmental variables.